Pembelajaran Berbasis Riset dengan Memanfaatkan Google Classroom pada Mahasiswa Tadris IPS IAIN Parepare - Fawziah Zahrawati; Andi Aras (IAIN Manado, 2020)
Interest in learning and learning outcomes are two important aspects in supporting the success of the learning process. This study aims to determine the effectiveness of Research-Based Learning by utilizing Google Classroom in improving student learning outcomes and interest in learning. This type of research is a pre-experimental research with One-Group Posttest Design. The data analyzed were data on learning outcomes and student interest in learning. Based on the results of the analysis of the posttest student learning outcomes using the t-test obtained that the p-value = 0.005 so that H1 was accepted and the results of the analysis of the posttest of student learning interest using the t-test obtained that the p-value = 0.000 so that H1 was accepted. Therefore, it can be stated that Research Based Learning by utilizing Google Classroom is effective in improving student learning outcomes and interest in learning.